The Impact of River Water Quality on Women's Health in Blankahan Village: Physico-Chemical Analysis and Social Health Analysis - Muhammadin Hamid; Nursal; Agus Nurbillah; Aulia Anggriani Lubis; Ayu Wahyuni Batubara; Eva Purwanti; Nazwa Armi; Hadi Wijoyo (Talenta Publisher, 2025)
River water plays an important role in human life. Along with the increasing population and waste problems generated from human activities, climate change is a factor that also affects river water quality. Blankahan Village is located in Langakat District, with 3 interconnected rivers, Palma River, Pekan Kuala, and Dosi Valley. This program examines the impact of river water quality on public health in Blankahan Village, with a focus on physico-chemical and social health analysis to support the achievement of SDGs points 3 and 6. It was found to be in a fairly poor and murky condition according to the classification according to Government Regulation Number 22 of 2021. Furthermore, based on statistical tests and One Way ANOVA Tests indicated that there was no statistically significant difference in the mean perception among the age groups. Some indicated women's health problems due to river water use such as dermatitis, skin diseases, and diarrhea continue to increase. River water sources are still used by some communities to fulfill household needs during the dry season despite many negative perceptions that river water quality is poor, dirty and polluted with waste. River water quality is influenced by seasonal factors and pollution, namely the difference in river water quality during the rainy and dry seasons, and is also caused by domestic waste, livestock waste, and industrial waste entering the water.